Pre-operative Embolization as Resection Strategy in Brain Tumor with No Neurological Deficit - Andi N. Sendjaja; Yogi Rosbianto; Agung B. Sutiono; Bilzardy F. Zulkifli; Roland Sidabutar; Achmad Adam; Muhammad Z. Arifin (Journal of Medicine and Health, 2018)
Meningioma is an intracranial tumor that generally involves meninges. This tumor canbe found along the dura layers at the skull base. Meningioma has vast vascularization from thearteries near dura attachment. Pre-operative embolization technique is an effective strategy toprevent intra-operative complications and better outcomes. The patient was a 24 year-oldwoman who has been complaining of headaches since 2 months ago. The CT Scan resulted in a12 x 9 x 7 cm isodense mass in the left temporoparietal enhanced homogenously by contrast.Pre-operative embolization was performed on the tumor feeding artery as a strategy to preventintra-operative blood loss. A left frontotemporosphenoidal craniotomy was performed 10 daysafter embolization to remove the tumor. A complete resection was successfully achieved withless intraoperative blood loss and without complication. The pathology examination resulted inmeningotheliomatous meningioma. A follow-up picture showed no recurrent tumor afterresection and the patient had no symptoms and neurological deficits until 6 months after thesurgery. In conclusion, meningioma is a common intracranial tumor with a lot of blood supply.However, tumor resection can be safely and efficaciously performed with good pre-operativestrategy.Keywords: brain tumor, embolization, meningioma, resection, skullbase